2019
DOI: 10.1158/0008-5472.can-18-2409
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fatty Acid Scavenging and Glycerophospholipid Metabolism Accompany Melanocyte Neoplasia Progression in Zebrafish

Abstract: Alterations in lipid metabolism in cancer cells impact cell structure, signaling, and energy metabolism, making lipid metabolism a potential diagnostic marker and therapeutic target. In this study, we combined PET, desorption electrospray ionization-mass spectrometry (DESI-MS), nonimaging MS, and transcriptomic analyses to interrogate changes in lipid metabolism in a transgenic zebrafish model of oncogenic RAS-driven melanocyte neoplasia progression. Exogenous fatty acid uptake was detected in melanoma tumor n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…The most common in vivo metabolic imaging modality currently used for metabolic imaging is FDG-PET to measure glucose uptake with a radiolabeled glucose tracer [20]. Previous studies outside of breast cancer have validated the use of an additional radio-labeled PET tracer, 18F-fluoro-6-thia-heptadecanoic acid (18F-FTHA), for in vivo fatty acid uptake measurements for myocardium imaging [21], and, more recently, for prostate cancer [22] and melanoma [23]. Though metabolic imaging through PET has proved valuable, especially in the clinic, its millimeter-scale resolution prevents capture of tumor heterogeneity [24,25], which tend to be under 1 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The most common in vivo metabolic imaging modality currently used for metabolic imaging is FDG-PET to measure glucose uptake with a radiolabeled glucose tracer [20]. Previous studies outside of breast cancer have validated the use of an additional radio-labeled PET tracer, 18F-fluoro-6-thia-heptadecanoic acid (18F-FTHA), for in vivo fatty acid uptake measurements for myocardium imaging [21], and, more recently, for prostate cancer [22] and melanoma [23]. Though metabolic imaging through PET has proved valuable, especially in the clinic, its millimeter-scale resolution prevents capture of tumor heterogeneity [24,25], which tend to be under 1 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of glycerophospholipid biosynthesis by a key enzyme of lysophosphatidic acid acyltransferase β (LPAAT-β) may be a potential therapeutic target for osteosarcoma patients [34]. Henderson et al found that glycerophospholipid metabolism is enhanced in melanocyte neoplasia in zebrafish where it accelerates tumour progression [35]. Enrichment analysis results show that biosynthesis and metabolism of glycerophospholipids are among the biological pathways involved in cancer progression.…”
mentioning
confidence: 99%
“…Interestingly, it was reported that melanoma-derived microvesicles favor the establishment of metastasis in a PS-dependent manner, possibly by downregulating the host's inflammatory immune responses [59]. Moreover, lipidome analyses revealed aberrant GPL metabolism with increased levels of PE and PC species in zebrafish V12RAS-driven melanoma [60]. Importantly, several studies have shown that cancer cells undergoing EMT have increased PC content and that phosphatidic acid (PA), a key intermediate metabolite in the synthesis of GPL, could maintain the stemness of cancer cells, by reducing apoptosis [61].…”
Section: Glycerophospholipids: Potential Roles In Melanoma Progression and Therapeutic Approachesmentioning
confidence: 99%